Acrylate-based coatings to protect lead substrates. (1st March 2017) - De Keersmaecker, Michel; Hauffman, Tom; van den Berg, Otto; Vandewalle, Stef; Muselle, Thibault; Verbeken, Kim; Hubin, Annick; Du Prez, Filip; Adriaens, Annemie
Highlights: A new acrylate coating for lead was developed using RAFT polymerization. Lead reacts with carboxylic acid groups of the polymer to form an asymmetric bridging bidentate bond. Multisine impedance measurements are used to rapidly screen the coatings. A higher acrylic acid content forms a thicker coating, but shows a faster electrolyte uptake. The molecular weight has a huge influence on the coating's stability and protective properties. Abstract: This study investigates the surface protection treatment of hydrophobic acrylate-based polymers with built-in carboxylic acid groups produced using a controlled Reversible Addition Fragmentation chain Transfer (RAFT) polymerization. The synthesized polymers are dissolved in a water-organic solvent mixture and afterwards deposited on lead substrates by immersing them in the solution. The coatings produce a hydrophobic film, which slows down the lead corrosion processes. The protective properties of the coatings are analyzed using non-destructive odd random phase multisine electrochemical impedance spectroscopy (ORP-EIS) in an acetic acid corrosive solution containing tertbutylammonium bromide (TBAB) supporting electrolyte. The impedance data and electron images of the coatings demonstrate that the coating thickness, pore formation, diffusion and electrolyte uptake profile depend on the polymer's acrylic acid content and the molecular weight. All these parameters have a clear impact on the inhibition of the corrosion process.